Lung pathology in slaughtered sheep from the north of the department of Bolivar, Colombia (2017)
The main objective of this study was to describe the lung lesions in slaughtered sheep. A cross-sectional descriptive study that included 26 sheep lungs without clinical signs of disease from the north of the department of Bolivar, Colombia, was carried out. The relative frequency of macroscopic and microscopic lung lesions, as well as the association between macroscopic lesions and body condition were established. Ninety-two percent of the sheep studied showed macroscopic and microscopic lesions. Thirty-two macroscopic lesions were found: pleuritis (34 %), interstitial pneumonia (32 %), embolic pneumonia (13 %), granulomatous pneumonia (6 %), emphysematous bulla (6 %), verminous pneumonia (3 %), suppurative bronchopneumonia (3 %) and atelectasis (3 %). Pleuritis showed a highly significant relationship with body condition (p value <0.01). Forty-one microscopic lesions grouped as inflammatory disorders (63 %), insufflation disturbances, i.e. emphysema and atelectasis (7 %), cell growth disorders (22 %), and microcirculatory disturbances (8 %) were observed. Regarding microscopic lesion chronicity, acute (29 %), subacute (32 %), chronic (37 %) and chronic-active (2 %) lesions were found. This is the first study in Colombia that describes lung lesions in slaughtered sheep. This study concludes that most lesions associated with the respiratory complex are subclinical, and therefore, it is necessary to strengthen the use of diagnostic and control measures to reduce infection rate and economic losses.